Speed star - Zucker, Jonny (Keystone books, 2007)
While looking for his running shoes before a race at school, fifteen-year-old Rex Jones is transported by his mysterious cell phone to the Olympics, where a strange man gives him a new pair of shoes just before he competes in the 100-meter final.